Low Dose Combined Treatment with Ultraviolet-C and Withaferin a Enhances Selective Killing of Oral Cancer Cells - Sheng-Yao Peng; Yen-Yun Wang; Ting-Hsun Lan; Li-Ching Lin; Shyng-Shiou F. Yuan; Jen-Yang Tang; Hsueh-Wei Chang (MDPI AG, 2020)
Withaferin A (WFA), a Withania somnifera-derived triterpenoid, is an anticancer natural product. The anticancer effect of nonionizing radiation such as ultraviolet-C (UVC) as well as the combined treatment of UVC and WFA is rarely investigated. Low dose UVC and/or WFA treatments (12 J/m2 and/or 1 μM) were chosen to evaluate antioral cancer cell line effects by examining cytotoxicity, cell cycle disruption, apoptosis induction, and DNA damage. For two cancer cell lines (Ca9-22 and HSC-3), single treatment (UVC or WFA) showed about 80% viability, while a combined treatment of UVC/WFA showed about 40% viability. In contrast, there was noncytotoxicity to normal oral cell lines (HGF-1). Compared to single treatment and control, low dose UVC/WFA shows high inductions of apoptosis in terms of flow cytometric detections for subG1, annexin V, pancaspase changes as well as Western blotting for detecting cleaved poly (ADP-ribose) polymerase (c-PARP) and caspase 3 (c-Cas 3) and luciferase assay for detecting Cas 3/7 activity. Low dose UVC/WFA also showed high inductions of oxidative stress and DNA damage in terms of flow cytometric detections of reactive oxygen species (ROS), mitochondrial superoxide (MitoSOX) generation, and membrane potential (MitoMP) destruction, γH2AX and 8-oxo-2'deoxyguanosine (8-oxodG) types of DNA damages. For comparison, low dose UVC/WFA show rare inductions of annexin V, Cas 3/7 activity, ROS, MitoSOX, and MitoMP changes to normal oral HGF-1 cells. Therefore, low dose UVC/WFA provides a novel selectively killing mechanism to oral cancer cells, suggesting that WFA is a UVC sensitizer to inhibit the proliferation of oral cancer cells.